Respuesta :
first, you try to get all your variables to one side of the equation, then solve:
-8 + 1 - 2 = 9x -6x
-9 = 3x
-9/3 = x
-3 = x
so, x = -3
-8 + 1 - 2 = 9x -6x
-9 = 3x
-9/3 = x
-3 = x
so, x = -3
You would first have to simplify the right hand side so it should look like this
"6x-8=9x+1"
Then you would have to move all of the terms containing x to the left hand side of the equation so it should look like this now
"-3x-8=1"
Now after that you would have to move all of the terms not containing x to the roght hand side of the equation so it should look like this now
"-3x=9"
Now you have to divide each term in -3x=9 by -3 to completely eliminate the fractions. So the answer should turn out as this
"x= -3
"6x-8=9x+1"
Then you would have to move all of the terms containing x to the left hand side of the equation so it should look like this now
"-3x-8=1"
Now after that you would have to move all of the terms not containing x to the roght hand side of the equation so it should look like this now
"-3x=9"
Now you have to divide each term in -3x=9 by -3 to completely eliminate the fractions. So the answer should turn out as this
"x= -3